2000
DOI: 10.1017/s1431927600037478
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive video imaging for interrogating pharmaceutical crystallization processes

Abstract: Crystallization is fundamental to much drug manufacture. Consequently a great deal of attention is focused on trying to attain a reproducible, robust process with predictable outcomes.Crystallization may be interrogated by various means including laser light scattering, infra-red spectroscopy, calorimetery, x-ray diffraction, solid state NMR analysis and optical and electron microscopy. Although laser backscattering is applicable to real time, in-situ studies it detects chord length an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…In recent years, several research groups and industrial companies have found that it is feasible to use on‐line two‐dimensional (2‐D) imaging for particle shape measurement, and initiated research activities . Rawlings and coworkers performed research on the measurement of crystal size and shape distributions using on‐line video images .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several research groups and industrial companies have found that it is feasible to use on‐line two‐dimensional (2‐D) imaging for particle shape measurement, and initiated research activities . Rawlings and coworkers performed research on the measurement of crystal size and shape distributions using on‐line video images .…”
Section: Introductionmentioning
confidence: 99%
“…Rawlings and coworkers performed research on the measurement of crystal size and shape distributions using on‐line video images . Wilkinson et al from GlaxoSmithKline developed a prototype on‐line, noninvasive microscopy imaging system for monitoring pharmaceutical crystallization. AstraZenaca tested the use of a commercially available imaging probe named as particle vision and measurement (PVM).…”
Section: Introductionmentioning
confidence: 99%
“…The on‐line imaging system employed in the experiments is a prototype system developed by research scientists at GlaxoSmithKline, UK31, the system is depicted in Figure 3. A CCD camera fitted with Navitar Precise Eye/Mitutoyo optics is employed for image acquisition with a maximum frequency of up to thirty images per second with a pixel resolution of 640 x 480 and a field of view from 140μm to 16mm dependent on calibrated lenses employed.…”
Section: The Experimentsmentioning
confidence: 99%
“…For online characterization of crystal shape, recent studies on video imaging have attracted much attention, which resulted in the development of some new instrument products such as the process vision and measurement (PVM) system,1 the particle image analyzer (PIA),2 in situ particle viewer (ISPV),3 and the online microscopy system of GlaxoSmithKline 4–6. Several research groups across Europe, USA and Asia have explored the use of these systems for crystallization process monitoring and control.…”
Section: Introductionmentioning
confidence: 99%
“…Scott et al7 used an inline camera prototype for qualitative monitoring of industrial crystallization. Wilkinson et al6 from GlaxoSmithKline were also among the first researchers to study online imaging for monitoring crystallization processes. Barrett and Glennon used the PVM imaging probe in the determination of the metastable zone of an inorganic compound 8.…”
Section: Introductionmentioning
confidence: 99%